Laboratory Experiments on the Effect of Microtopography on Soil-Water Movement: Spatial Variability in Wetting Front Movement - Leif Sande; Xuefeng Chu (Applied and Environmental Soil Science)
The effect of microtopography on soil-water movement is a topic of interest for a range of disciplines, with experimental studies investigating the relationship between the two lacking. Laboratory experiments were conducted by simulating rainfall across packed soil surfaces to investigate the effect of microtopography on wetting front movement within experimental soil profiles. In small soil box experiments, the observed wetting fronts for soil profiles showed considerably deeper movement beneath a smooth surface than depressions for 12–60 min rainfalls. For large soil box experiments, the wetting front reached moisture sensors installed at 5 and 10 cm depths and corresponding to various rough and smooth surface features at significantly different times, with movement being most rapid beneath the smooth surface. Wetting front movement was “quicker” beneath surface peaks than depressions for the rough surface as attributed to 2D/3D unsaturated flow. This study provides valuable experimentally based insight into the effect of microtopography on soil-water movement.